Spectrophotometric determination of leukocytes in urine - OGAN, AYŞE (WILEY, 2004)
A spectrophotometric method based on myeloperoxidase activity for the determination of leukocytes in urine is described. Red cells that may be found in urine samples were lysed by an ammonium chloride method. Leukocytes were then sedimented by centrifugation and lysed using Triton X-100 (Sigma Chemicals Co., St. Louis, MO). Myeloperoxidase-catalyzed oxidation of o-dianisidine was carried out at 37degreesC, pH 7. The reaction was stopped with the addition of 2 M H2SO4, and a stable form of oxidized o-dianisidine in acidic solution was obtained. Solid particles that may be found in urine samples were removed by centrifugation to avoid turbidity, and absorbance values of the supernatants were recorded at 400 rim. An Average number of leukocytes were noted per number of fields by microscopic examination and were related with the absorbance values of the supernatants at 400 nm. Pearson correlation (r) between our presented spectrophotometric analysis results and visual microscopic analysis was 0.877. Roche Combur 10-test M strips (Roche, Mannheim, Germany) and Multistix 10 SG Bayer test strips (Bayer Diagnostics, UK) were 0.645 and 0.648, respectively (P < 0.0001). (C) 2004 Wiley-Liss, Inc.
Keywords: leukocyte; determination; urine; spectrophotometry; o-dianisidine; 5-LIPOXYGENASE ACTIVITY; EOSINOPHIL PEROXIDASE; HUMAN-NEUTROPHILS; SINGLET OXYGEN; TEST STRIPS; MYELOPEROXIDASE; URINALYSIS; OXIDATION; CHLORIDE; BROMIDE